Low cycle fatigue behavior of salt coated and pre-exposed IN-617 alloy - Rao C.V.; Srinivas N.C.S.; Sastry G.V.S.; Singh V. (My University, 2025)
The present investigation deals with low cycle fatigue (LCF) behavior of the IN-617 alloy, after oxidation at 850 °C for varying durations, without and with mixed salt coating. LCF tests were conducted under fully reversed axial strain controlled mode at a strain rate of 5 × 10−3 s−1 and strain amplitude of ±0.25% at 850 °C to examine the influence of oxidation and mixed salt coating of 10%NaCl+90%Na2SO4, on fatigue life and deformation behavior under cyclic loading. Oxidation of the samples up to 1000 h did not show any significant effect on fatigue life, whereas fatigue life of the salt coated and pre-exposed samples was drastically reduced with increase in duration of the exposure. Stress amplitude decreased with increase in the duration of the exposure. Salt coated samples exhibited lower stress amplitude compared to that of the oxidized samples. XRD analysis and Electron Probe Micro Analysis (EPMA) elemental mapping confirmed formation of effective Cr2O3 layer on the surface and Al2O3 layer beneath the surface which provided good oxidation resistance at this temperature. The depth of oxide layer increased with increase in the duration of oxidation. Under salt environment, these oxide layers were broken and the substrate was exposed to corrosive environment, which caused severe intergranular hot corrosion of the samples. The depth of intergranular corrosion was increased with increase in the duration of exposure. Chromium sulphide was found to be the detrimental product formed along the grain boundaries and was the prime reason for rapid crack propagation and reduction in the fatigue life. © 2020 Elsevier Inc.